Quelles archives pour quelle histoire ? Enquêter sur le Fonds européen de développement depuis le Mali - Bouakary Ouattara (Revue Internationale des Études du Développement)
This article highlights the asymmetries of access and conservation of the European Development Fund’s archives in Mali for researchers based there. It analyzes the explanatory factors of these asymmetries, from the late implementation of legislation and of an archival policy in Mali, to the lack of interest among the staff in the services that produced documents, and the sensitive EDF-Mali archives, both politically and administratively. Lastly, the article examines the consequences of these asymmetries on the writing of agricultural development history in Mali.